Jacques Ellul on Revolution - Temple, Katharine C. (My University, 1972)
A recurrent theme throughout the writings of Professor Jacques Ellul, a prominent Protestant theologian and social thinker, has been the need for revolutionary action in the modern world. This thesis will first explicate what he means by calling Christianity a revolutionary faith. Then it will outline his social thought concerning the theory and practice of revolution. Finally, it will show how the two accounts fit together within his total plan. The main argument will be-that his social analysis concerning revolution is directly dependent on his revolutionary theology.
Keywords: Religion; Religion